2016
DOI: 10.1121/1.4962557
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis and modeling of 255 source levels of merchant ships from an acoustic observatory along St. Lawrence Seaway

Abstract: An ensemble of 255 spectral source levels (SSLs) of merchant ships were measured with an opportunistic seaway acoustic observatory adhering to the American National Standards Institute/Acoustical Society of America S12.64-2009 standard as much as possible, and deployed in the 350-m deep lower St. Lawrence Seaway in eastern Canada. The estimated SSLs were sensitive to the transmission loss model. The best transmission loss model at the three measuring depths was an empirical in situ function for ranges larger t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 24 publications
6
35
0
2
Order By: Relevance
“…For Cargo and Tanker the variability of the measured source strengths is in the range of 20-30 dB above ∼200 Hz while increasing to >40 dB at around 100 Hz, agreeing with what is observed by Simard et al (2016). The observed Passenger ships notably show a smaller variability, not exceeding 20 dB for frequencies >200 Hz.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…For Cargo and Tanker the variability of the measured source strengths is in the range of 20-30 dB above ∼200 Hz while increasing to >40 dB at around 100 Hz, agreeing with what is observed by Simard et al (2016). The observed Passenger ships notably show a smaller variability, not exceeding 20 dB for frequencies >200 Hz.…”
Section: Resultssupporting
confidence: 75%
“…For the seabed, less high resolution data are available and estimates of the seabed structure and parameters were determined by a dedicated transmission loss measurement and geo-acoustic inversion. The approach is similar to that by Simard et al (2016), but employs a more elaborate procedure for estimating the seabed parameters motivated by the relative shallowness of the observation site (∼ 40 m). Furthermore, a wider range of ship types are included in the analysis, covering both passenger ferries and tugboats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface-corrected broadband source levels (5-1000 Hz) may be derived from the surface-affected levels reported by McKenna et al (2012b) by adding 20 to 27 dB. This might explain why the surfaceaffected broadband source levels reported by McKenna et al (2012b) were found to be more than 15 dB lower than the source levels observed by Simard et al (2016). In addition, the inclination-angle dependence of the surface-affected source levels might further explain why at an inclination angle of about 0.2 (8 m depth) (Veirs et al, 2016) observed lower source levels (up to 15 dB) than McKenna et al (2012b) at 10 and Arveson and Vendittis (2000) at 90…”
Section: Discussionmentioning
confidence: 99%
“…Šiuo metu yra žinoma nemažai sudėtingų fizikinių povandeninio triukšmo modelių (Jensen et al 2011;Carey, Evans 2011;Etter 2012), tačiau supaprastintų priemonių, skirtų povandeniniam triukšmui modeliuoti bei aplinkos būklei vertinti, vis dar yra nedaug (Erbe et al 2012). Šiuo tikslu Klaipėdos universitete buvo pradėtas kurti supaprastintas povandeninio triukšmo modelis, kurį taikant galima prognozuoti laivų sukeliamo triukšmo lygius erdvėje, pasitelkiant jau turimą kitų šalių patirtį (Erbe et al 2014;Gervaise et al 2015;Simard et al 2016). Šio modelio programavimas buvo suskirstytas į 3 etapus: 1) programinio modulio, skirto automatinės identifikavimo sistemos (AIS) laivų registravimo duomenims apdoroti bei laivų triukšmo lygiams (GSL) tiriamoje vietovėje apskaičiuoti, sukūrimas; 2) modulio, skirto triukšmo lygių vidurkiams apskaičiuoti priklausomą triukšmo sklidimą, įtraukiant mažo gylio atkirtimo dažnio bei žemo dažnio korekcijas; 3) apskaičiavo triukšmo lygių vidurkius bei statistinius duomenis langeliuose bei erdvinį duomenų tinklelį toliau apdoroti (kartografuoti).…”
Section: įVadasunclassified